In Memoriam: Mila A. Reforma (1943-2023) - Mangaoang, Eula (Philippine Journal of Public Administration; Vol 67 (2023)DO - 10.5281/zenodo.13836807, 2024)
Mila A. Reforma, 79, retired professor of public administration and former college secretary at the National College of Public Administration and Governance, University of the Philippines (UP-NCPAG), passed away on 27 July 2023.